Organizational trust: Mayer, Davis and Schoorman a review - Ferreira, Ana Teresa (2015)
Trust is a relevant variable in interpersonal relationships in organizations. This review intends to aggregate literature on trust, based specifically on the model by Mayer, Davis and Schoorman [1]. New developments and practice implications are discussed